STRESS, PHYSICAL ACTIVITY, AND DIETARY INTAKE ARE ASSOCIATED WITH DYSMENORRHEA AMONG FEMALE STUDENTS - Syamsudi, Nur Anindya; Mayasari, Noor Rohmah; Solihah , Lini Anisfatus (Indonesian Midwifery and Health Sciences Journal, 2024)
Background: The estimated prevalence of dysmenorrhea ranges from 45% to 93% of women of reproductive age. Approximately 10–15% of women complain about severe pain, resulting in a negative impact on their daily activities. Factors that cause dysmenorrhea are physical activity, nutritional status, dietary intake, stress, and body mass index. This study explores the prevalence of dysmenorrhea and investigates its correlation with physical activity, stress, and Dietary Intake among female students studying nutrition in Universitas Negeri Surabaya, Indonesia. Method: This research was cross sectional analytic descriptive study with minimum sample size of 114 female students. Primary data was collected using a set of questionnaires. Dysmenorrhea pain was assessed using the Numeric Rating Scale (NRS). Stress  levels were measured by employing  the Depression  Anxiety  Stress  Scales 42 (DASS 42). Physical activity using The International Physical Activity Questionnaire (IPAQ). Dietary data including intakes of energy, iron, folate, and B12 was assessed using non-consecutive 3x24 hours food records, representing 2 weekdays and a weekend. The data were analyzed using chi-square for category data and one-way anova for continuous data. Result: Dietary intake especially vitamin B12 (p=0.02) were associated to the level of dysmenorrhea, whereas stress (p=0.36) and physical activity (p=0.82) was not associated of dysmenorrhea. Conclusion: This study emphasized the high prevalence of dysmenorrhea among female college students studying Nutrition, revealing important connections between stress, physical activity and dietary intake. Additionally, the research revealed a significant relationship between dietary intake (vitamin B12) and dysmenorrhea.